2007
DOI: 10.1189/jlb.0506342
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 regulates pathological intraocular neovascularization

Abstract: Recently, the proinflammatory cytokine IL-18 has been shown to have a role in angiogenesis. This study aimed to elucidate its role in abnormal neovascularization (NV) in an oxygen-induced retinopathy (OIR) mouse model of the retinopathy seen in human premature newborns. IL-18 was constitutively expressed in the retina in C57BL/6 mice, but expression transiently dropped on Day 17 after birth in mice exposed to 75% oxygen for 5 days between Days 7 and 12. Coincident with the IL-18 reduction in oxygen-treated mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
1
29
2
Order By: Relevance
“…DM2 patients sera contained higher concentration of IL-18 and induced stronger neovascular reaction in mice skin than did the sera of corresponding control people (Skopinski et al, 2005). IL-18 regulates pathogenic retinal neovascularization by promoting its regression rather than inhibiting its development in an oxygen-induced retinopathy and is a useful, new approach to treating retinopathy in humans (Qiao et al, 2007).…”
Section: Il-18 Enhances Angiogenesismentioning
confidence: 99%
“…DM2 patients sera contained higher concentration of IL-18 and induced stronger neovascular reaction in mice skin than did the sera of corresponding control people (Skopinski et al, 2005). IL-18 regulates pathogenic retinal neovascularization by promoting its regression rather than inhibiting its development in an oxygen-induced retinopathy and is a useful, new approach to treating retinopathy in humans (Qiao et al, 2007).…”
Section: Il-18 Enhances Angiogenesismentioning
confidence: 99%
“…We and others have shown that IL-18 promotes endothelial cell migration and is a direct angiogenic mediator in vitro and in vivo 4 24 25. IL-18 induces hypoxia inducible factor-1α (HIF-1α) through the activity of the GTPase Rac1, and increases HIF-1α-mediated tumour progression and metastasis 26.…”
Section: Discussionmentioning
confidence: 99%
“…37 Interestingly, IL-18 regulates pathogenic retinal neovascularization by promoting regression of abnormal neovascularization in an oxygen-induced retinopathy mouse model. 38 Intraretinal and subretinal neovascularization were observed during EAU, 39 with an imbalance between VEGF and TGF-␀. 40 The role of IL-18 in EAU is not clearly identified.…”
Section: Figurementioning
confidence: 98%